ANALISIS REKONSILIASI FISKAL PT. NRW DALAM MENGHITUNG PPH BADAN TERUTANG TAHUN 2021 - Tannia, Clarita; Widjaja, Purnamawati Helen (Jurnal Paradigma Akuntansi, 2025)
The aim of this study is to determine whether PT. NRW has carried out fiscal reconciliation in accordance with applicable current tax regulations and how to calculate the amount of income tax for PT. NRW after analysis. The research subjects in this study is PT. NRW. The research object used are the financial statements of PT. NRW 2021 according to commercial and fiscal, calculation of corporate income tax payable, as well as Article 28A/29 income tax. This study used a descriptive research design by collecting data through field research (observations and interviews) on the company and library research. The results of this study state that there are several fiscal corrections made by companies that are not in accordance with applicable current tax regulations so that there are differences in the calculation of taxable income and corporate income tax payable after analysis.